IMPLEMENTASI NILAI-NILAI PROFETIK DALAM KEPEMIMPINAN MODERN PADA MANAJEMEN KINERJA DI PERGURUAN TINGGI ISLAM SWASTA KOTA METRO - Kusuma Dewi, Indah (Universitas Islam Negeri Raden Intan Lampung, 2019)
Leadership in Islam has a very strategic position in the realization of the application of Islamic principles in living systems. Allah SWT Set an example for the people of the leadership of the Prophet Muhammad, because he is a leader who is holistic (comprehensive), accepted (accepted), and proven (proven). But Muslim leaders today prefer to refer to the leadership model that was conceived and practiced in the country West. This is the basis of this study with the aim to find out the Implementation of Prophetic Leadership Values in Performance Management in Metro City Private Islamic Colleges. Where the values of prophetic leadership here are the values of leadership in the Prophet who were developed in modern times the 4 roles of leadership namely: pioneers (pathfinding), aligning, empowering, modeling.